2020
DOI: 10.1097/md.0000000000022209
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ginkgo preparation in patients with vascular dementia

Abstract: Background: Vascular dementia has become the second most common type of dementia after Alzheimer disease. At present, there is no uniform standard for VaD treatment guidelines among countries. The efficacy of ginkgo biloba in the treatment of vascular dementia is still controversial. The purpose of this study is to evaluate the effectiveness and safety of ginkgo biloba in the treatment of vascular dementia through meta-analysis. Methods: Six English databases (PubMed, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Otros estudios preclínicos y clínicos han demostrado el efecto positivo del ginkgo biloba para mejorar las capacidades cognitivas en personas con cierta discapacidad, así como para reducir los TAG (90)(91)(92) .…”
Section: Consecuencias De La Nutrición Y La Microbiota En Los Trastor...unclassified
“…Otros estudios preclínicos y clínicos han demostrado el efecto positivo del ginkgo biloba para mejorar las capacidades cognitivas en personas con cierta discapacidad, así como para reducir los TAG (90)(91)(92) .…”
Section: Consecuencias De La Nutrición Y La Microbiota En Los Trastor...unclassified
“…26 Furthermore, a meta-analysis study by Wang et al proved that Gb could be an effective treatment for vascular dementia. 27 Another meta-analysis study explored the efficacy of EGb 761 in dementia patients treated with 120 mg or 240 mg per day when compared to placebo. The study results showed that EGb 761 was well tolerated in all trials and that 240 mg of EGb 761 was more effective in improving cognition.…”
Section: Ginkgo Biloba (Gb) Lmentioning
confidence: 99%
“…This method can help summarize the evidence from multiple systematic reviews and meta‐analyses, assessing the strength of evidence and extent of possible biases to ascertain the quality of evidence. To date, several systematic reviews and meta‐analyses (SRMAs) focusing on the antidementia effects of herbal medicines and medicinal plants have been recently reported (Hussain et al, 2022; Liao et al, 2020; Wang et al, 2020; Zhu, Mei, Zhang, Xie, & Lang, 2019). To synthesise the most updated comprehensive evidence, we performed the umbrella review to systematically summarize the effects of various types of herbal medicines used for improving cognitive function in healthy volunteer or patients with dementia for determining benefits of each herb from previously published systematic reviews and meta‐analyses to provide the wide picture for real‐world clinical practice.…”
Section: Introductionmentioning
confidence: 99%